2011
DOI: 10.1007/s10658-011-9798-y
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale assessment of agricultural practices affecting Fusarium root rot and common bean yield

Abstract: The relationships between a number of agronomic practices, Fusarium root rot (FRR) measurements and yield variables were characterized at different growth stages in 122 commercial bean fields in Zanjan, Iran. Mean FRR incidence, severity and index differed among growth stages and years. A lower FRR index at growth stage R9 and higher yields were detected in Red beans compared to Pinto and White beans. FRR severity affected the number of pods and seeds per plant. Despite the lack of an impact of initial drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…In addition to being affected by the interrelationships among agronomic and soil variables, the relationship between bean wilt and its predictors is complicated by the fact that agroecological and pathological conditions can interact over a very wide range of temporal and spatial scales. For example, planting date had significant impact on bean Fusarium root rot (caused by F. solani) at early stages of plant growth, but not at flowering-podding and pod maturity stages (Naseri & Marefat 2011). Furthermore, regional findings in Zanjan did not support the significant influence of planting date on bean yield determined in a plot-scale basis experiment (Naseri & Mousavi 2013).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition to being affected by the interrelationships among agronomic and soil variables, the relationship between bean wilt and its predictors is complicated by the fact that agroecological and pathological conditions can interact over a very wide range of temporal and spatial scales. For example, planting date had significant impact on bean Fusarium root rot (caused by F. solani) at early stages of plant growth, but not at flowering-podding and pod maturity stages (Naseri & Marefat 2011). Furthermore, regional findings in Zanjan did not support the significant influence of planting date on bean yield determined in a plot-scale basis experiment (Naseri & Mousavi 2013).…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, bean resistance associated with appropriate cultural strategies may improve the effectiveness of disease management programs. Earlier reports evidenced that bean-Fusarium-root-rot pathosystems were affected by bean market class, crop planted before bean, date and depth of sowing, irrigation frequency, plant and weed density, urea usage, and soil factors such as pH, organic matter, rhizobial nodulation, texture, and fungicide-treatment of field soil (Naseri & Marefat 2011, Naseri 2014. For Fusarium wilt disease, effects of sowing date and cultivar in chickpeas (Navas-Cortés et al 1998), nitrogen fertilizer and soil pH in chrysanthemum (Woltz & Engelhar 1973), reservoir and non-reservoir hosts in beans (Dhingra & Coelho Netto 2001), and trifluraline in soybeans (Carson et al 1991) have been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…phaseoli (FSP) is a prevalent and economically important disease in the bean‐growing parts of the province and occurs in most Zanjan soils (Naseri ). In farms infested with FSP, bean yields have been decreased up to 52% (Naseri and Marefat ). It is believed that the development of root rot diseases is relatively dependent on certain agro‐ecological conditions (Schwartz and Pastor‐Corrales ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cropping methods can influence the degree to which bean plants are prone to Fusarium root rot (FRR) and can be manipulated to minimize the disease prevalence. In Zanjan, bean production is threatened by the following features presumably increasing the prevailing FRR risk: frequent irrigation, high plant and weed density, deep and early sowing, overuse of urea, growing bean in loamy soils, low soil organic matter, the lack of rhizobial root nodulation and soil treatment with improper fungicides such as benomyl (Naseri and Marefat ; Naseri ). A build‐up of soil and seed infestations and severe disease levels under optimum environmental and plant conditions for FSP may be the consequences of such a cropping system (Naseri ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation